2019
DOI: 10.3390/su11164310
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic Mean Divisia Index Decomposition of CO2 Emissions from Urban Passenger Transport: An Empirical Study of Global Cities from 1960–2001

Abstract: The urban transport sector has become one of the major contributors to global CO2 emissions. This paper investigates the driving forces of changes in CO2 emissions from the passenger transport sectors in different cities, which is helpful for formulating effective carbon-reduction policies and strategies. The logarithmic mean Divisia index (LMDI) method is used to decompose the CO2 emissions changes into five driving determinants: Urbanization level, motorization level, mode structure, energy intensity, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Index decomposition analysis (IDA) is an analytical tool that is used to measure different driving factors and their environmental side effects [40]. This method allows scientists to break down the aggregate indicator into a combination of several factors and to determine the influence of a single factor on the aggregate indicator [41]. In other words, the IDA method allows us to measure the impact of the main factors influencing changes over time in the GHG emissions produced by the agricultural sector.…”
Section: Methods and Used Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Index decomposition analysis (IDA) is an analytical tool that is used to measure different driving factors and their environmental side effects [40]. This method allows scientists to break down the aggregate indicator into a combination of several factors and to determine the influence of a single factor on the aggregate indicator [41]. In other words, the IDA method allows us to measure the impact of the main factors influencing changes over time in the GHG emissions produced by the agricultural sector.…”
Section: Methods and Used Datamentioning
confidence: 99%
“…The IDA method can be divided into the Divisia IDA method and the Laspeyres IDA method [39]. Although both of these methods are used in research, the Divisia index method is superior to the Laspeyres index method because in the process of decomposition, there are no residual terms [41]; it considers the change in factors over time [42]. Ang and Liu (2001) [43] improved the Divisia index method and proposed a logarithmic mean Divisia index (LMDI) with good decomposition and aggregation.…”
Section: Methods and Used Datamentioning
confidence: 99%
“…Index decomposition analysis (IDA) is a comprehensive mechanism that allows to identify the main drivers of change in environmental performance indicators [11]. The conceptual framework of IDA is based on the decomposition of the study phenomenon, breaking down the element of the research study into several factors to examine their influence on the outcome [12].…”
Section: Methodsmentioning
confidence: 99%
“…They found that the main factor behind carbon emissions growth is the transport sector. Tu et al ( 2019 ) employed LMDI decomposition to investigate the changes in carbon emissions of the transport sector from 1960 to 2001 in different cities. They suggested some effective strategies to reduce carbon emissions, such as rational land use, fuel economy policies, and the development of public transport.…”
Section: Literature Reviewmentioning
confidence: 99%